2017
DOI: 10.1016/j.clinthera.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns, Health Care Resource Utilization, and Spending in Medicaid Beneficiaries Initiating Second-generation Long-acting Injectable Agents Versus Oral Atypical Antipsychotics

Abstract: Medicaid beneficiaries with schizophrenia initiated on SGA-LAIs had better adherence and persistence to therapy over 12 months than patients initiated on OAAs. SGA-LAIs, particularly PP-LAI, were associated with lower medical costs that successfully offset more than one half of the higher pharmacy costs relative to OAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 23 publications
6
90
1
Order By: Relevance
“…Indeed, higher adherence to APs among patients with schizophrenia has been shown to be associated with improved adherence to other medications used to manage comorbidities in these patients [29,30]. Moreover, the improved adherence to APs postversus pre-PP1M transition was evident despite the fact that adherence pre-PP1M transition was higher than reported elsewhere [9,17,21]. By design, patients were required to have at least 30 days of treatment on oral risperidone or oral paliperidone in the 60 days prior to PP1M transition to exclude treatment-naïve patients, which may explain the higher adherence rates observed in the current study relative to other studies.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Indeed, higher adherence to APs among patients with schizophrenia has been shown to be associated with improved adherence to other medications used to manage comorbidities in these patients [29,30]. Moreover, the improved adherence to APs postversus pre-PP1M transition was evident despite the fact that adherence pre-PP1M transition was higher than reported elsewhere [9,17,21]. By design, patients were required to have at least 30 days of treatment on oral risperidone or oral paliperidone in the 60 days prior to PP1M transition to exclude treatment-naïve patients, which may explain the higher adherence rates observed in the current study relative to other studies.…”
Section: Discussionmentioning
confidence: 90%
“…Findings from this study are consistent with previous studies showing that switching from oral OAAs to LAIs could help improve adherence and outcomes by reducing dosing frequency. A large real-world cohort study of Medicaid patients with schizophrenia showed that patients initiated on second-generation LAIs had better adherence to and persistence with therapy over 12 months compared to those initiated on OAAs [17]. Similarly, in Medicaid patients recently diagnosed with schizophrenia in the US, treatment with PP1M versus OAAs was associated with better adherence, lower use of other psychiatric medications (i.e., antidepressants, anxiolytics, and mood stabilizers), and reduced medical costs resulting from fewer days spent in an inpatient setting [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Pilon et al ., persistence to the index treatment (oral SGA, ARI‐LAI, RIS‐LAI, and PP) was defined as having a continuous supply of available medication with no gaps for ≥30, 60, or 90 days and was assessed at 12 months post‐index date. There were no clear differences in the discontinuation rates between the groups.…”
Section: Resultsmentioning
confidence: 99%
“…In a population of patients diagnosed with SCZ spectrum-disorders, Limonsin et al found that the proportion of patients who discontinued pharmacological treatment was significantly higher in the RIS-LAI group than in the PP group. 93 In the study by Pilon et al, 94 persistence to the index treatment (oral SGA, ARI-LAI, RIS-LAI, and PP) was defined as having a continuous supply of available medication with no gaps for ≥30, 60, or 90 days and was assessed at 12 months post-index date. There were no clear differences in the discontinuation rates between the groups.…”
Section: Pubmed Cochrane Librarymentioning
confidence: 99%